2020
DOI: 10.18805/lr-4440
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Selection for Resistance against Charcoal Rot Disease of Soybean [Glycine max (L.) Merrill] Caused by Macrophomina phaseolina (Tassi) Goid

Abstract: Background: Soybean is an important oilseed crop. Charcoal rot caused by soil borne polyphagous fungus Macrophomina phaseolina in soybean causes about 80 percent yield loss. Methods: Callus and cell suspension cultures derived from immature and mature embryonic axis and cotyledons explants from disease susceptible soybean cultivars (cv JS335 and JS95-60) were treated with purified toxic culture filtrate generated by the fungus Macrophomina phaseolina fortified with MS culture medium. A continuous method of fou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

7
3

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Cell suspension culture may be used to select valuable mutant cell lines through in vitro selection [28][29][30][31] for useful secondary metabolites [32][33][34]. It could also be employed for genetic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…Cell suspension culture may be used to select valuable mutant cell lines through in vitro selection [28][29][30][31] for useful secondary metabolites [32][33][34]. It could also be employed for genetic transformation.…”
Section: Introductionmentioning
confidence: 99%
“…The preference of genetically assorted parents for hybridization progrms is an imperative feature of any crop improvement program to accomplish enviable sergeants [46][47][48][49][50][51]. Since the identification of morphological data-based variation is important for effective evaluation and utilization of genotypes in a breeding program, screening is the only valid way to develop new genotypes for cultivation [46,[52][53][54]. It is demonstrated that the mustard genotypes used in this study have high genetic variability which makes them potential genotypes to foster new cultivars through future mustard breeding.…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, except for a few, the contribution of in vitro selection in conjunction with somaclonal variation procedures in the breeding program in Brassica juncea is narrow [16], especially for erucic acid. Nonetheless, encouraging reports have been evidenced in wheat and barley [21], soybean [22][23][24][25], groundnut [26][27][28], onion [29], and Withania somnifera [30] with variable degrees of successes.…”
Section: Introductionmentioning
confidence: 99%